Kontribusi Luas Panen terhadap Produksi Padi: Studi Kasus Kabupaten Gorontalo Menggunakan Analisis Regresi Sederhana - La Alio; Iswan Dunggio; Hasim Hasim; Sukirman Rahim (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia, as an archipelago, has significant agricultural potential, but its optimal utilization requires balancing rice production volume with the available harvest area. This study analyzed the contribution of harvested area to rice production in Gorontalo Regency using linear regression analysis. The data used included the harvest area and the amount of rice production during the period 2018–2024, sourced from the Central Bureau of Statistics (BPS) of Gorontalo Province. The independent variable in this study was the amount of rice production (tonnes), while the dependent variable was the area of harvest (Ha). The analysis results revealed a very strong linear relationship between the two variables, with a correlation coefficient (R) of 0.8437 and a coefficient of determination (R²) of 0.7119. The regression equation indicated that an increase in rice production by 4.8891 tonnes corresponded to an increase in the harvested area by 1 hectare. The model significance value of 0.017017 indicated that the regression model was statistically significant. This finding demonstrates that the amount of rice production significantly affects the area of harvest, and the model can serve as a predictive basis for planning agricultural sector policies in Gorontalo Regency.